2017
DOI: 10.1016/j.neuroimage.2016.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the neural effects of cognitive bias modification training

Abstract: Cognitive bias modification (CBM) was first developed as an experimental tool to examine the causal role of cognitive biases, and later developed into complementary interventions in experimental psychopathology research. CBM involves the "re-training" of implicit biases by means of multiple trials of computerized tasks, and has been demonstrated to change anxious, depressive and drug-seeking behavior, including clinically relevant effects. Recently, the field has progressed by combining CBM with neuroimaging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 137 publications
(242 reference statements)
2
26
0
Order By: Relevance
“…23 Overall, these early results provide some evidence that ABM modifies function in emotional regulatory systems although the small study sample sizes and variety of approaches used may underpin the absence of consistent effects across studies. 24 No study has investigated ABM-induced changes in emotion processing using fMRI in a large clinical sample after multiple training sessions. In this pre-registered clinical trial (NCT02931487) we used a sample of 134 participants previously treated for depression and with various degrees of residual symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…23 Overall, these early results provide some evidence that ABM modifies function in emotional regulatory systems although the small study sample sizes and variety of approaches used may underpin the absence of consistent effects across studies. 24 No study has investigated ABM-induced changes in emotion processing using fMRI in a large clinical sample after multiple training sessions. In this pre-registered clinical trial (NCT02931487) we used a sample of 134 participants previously treated for depression and with various degrees of residual symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…First, as stated earlier, future research could explore the crucial characteristics that might enhance the effectiveness of CBM, especially in real-world settings, and clarify the functional relationship between CBM and different facets of SAD symptomatology. Recently, a review on the neural effects of CBM for anxiety, addiction, and depression was published in NeuroImage , which included a total of 13 published studies that used (functional) magnetic resonance imaging (MRI) or electroencephalography as an outcome measure; 5 of these studies were on social anxiety [110]. Future studies could thus adopt some techniques commonly used in cognitive neuroscience (i.e., fMRI) to explore the possible neurobiological basis of CB in SAD.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological mechanisms that underpin the behavioural effects of CAT are fairly well-understood: the reversal of automatic approach bias (Eberl et al 2013) and, in particular, the strengthening of automatic alcohol-avoidance associations (Gladwin et al 2015) can account for the beneficial effects of CAT on long-term outcomes in alcohol-dependent patients. However, the brain mechanisms that underlie these changes in alcohol-avoidance and alcohol-approach associations after CAT have only recently been investigated, and they remain poorly understood (den Uyl et al 2016a, b;Ferrari et al 2018;Wiers et al 2014;Wiers and Wiers 2016). Two fMRI studies demonstrated reduced activation in the amygdala (Wiers et al 2015b) and in the mPFC (Wiers et al 2015a) in alcohol-dependent patients after multiple sessions of CAT, which is suggestive of a blunting of activity in neural substrates of alcohol cue reactivity (Schacht et al 2013).…”
Section: Introductionmentioning
confidence: 99%